Covid-19 and capitalism : Success and failure of the legal methods for dealing with a pandemic - Byttebier, Koen, 1966-; Vrije Universiteit Brussel; Van der Borght, Kim, ....- (Cham : Springer, 2022)
This open access book provides a comprehensive analysis of the socioeconomic determinants of covid-19. From the end of 2019 until presently, the world has been ravaged by the Covid-19 pandamic. Although the cause of this is a virus, the extent to which this virus spread, and therefore the number of infections and deaths, was largely determined by socio-economic factors.
Keywords: Capitalisme; Covid